2011
DOI: 10.1177/0145482x1110500404
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Tactile Maps and Haptic Digital Representations of a Maritime Environment

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
(13 reference statements)
0
7
0
2
Order By: Relevance
“…Then, we used the same spatial configuration for each map but rotations of thirty degrees were applied to the initial configuration to produce new maps and avoid any learning effect (see Figure 2). The POIs used during the familiarization phase were named A-F. For the different online tasks, the six POIs were numbers with two digits (i.e., [11][12][13][14][15][16] for Map #1, and 21-26 for Map #2). For the offline tasks, the names of the POIs were real names, but not names that can typically be found on maps (see Table 1).…”
Section: Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we used the same spatial configuration for each map but rotations of thirty degrees were applied to the initial configuration to produce new maps and avoid any learning effect (see Figure 2). The POIs used during the familiarization phase were named A-F. For the different online tasks, the six POIs were numbers with two digits (i.e., [11][12][13][14][15][16] for Map #1, and 21-26 for Map #2). For the offline tasks, the names of the POIs were real names, but not names that can typically be found on maps (see Table 1).…”
Section: Mapsmentioning
confidence: 99%
“…As suggested by Ducasse et al [12], accessible interactive maps can be divided in two families: Hybrid Interactive Maps (HIMs) that include both a digital and a physical representation, and Digital Interactive Maps (DIMs) that are maps displayed on a flat surface such as a screen. Many prototypes of DIMs and HIMs have proven to be efficient for the acquisition of spatial knowledge in blind people [13][14][15], but, in comparison to HIMs, DIMs clearly miss tactile cues that ease non-visual exploration. However, they also present advantages.…”
Section: Introductionmentioning
confidence: 99%
“…These multimodal maps, usually incorporating auditory cues and/ or text-to-speech descriptions coupled with a tactile display, have been shown to be extremely beneficial in supporting BVI spatial behaviors, such as route planning, learning landmark relations, wayfinding, and cognitive mapping. Some examples of multimodal maps that have been tested with BVI users include systems employing a physical map overlay [49,50], a force feedback haptic device [51,52], a dynamic pin array [53,54], and most recently, touchscreen-based vibrotactile feedback [11,14,15]. Approaches utilizing this latest class of multimodal map have demonstrated learning of road networks [11], floor maps of university buildings [14], as well as simple street maps using both mobile and watch-based interfaces [15].…”
Section: Related Workmentioning
confidence: 99%
“…Crossan and Brewster demonstrated that the combination of force feedback from a PHANTOM Omni device, with sound feedback and a tactile pin array for specifying the direction, was effective in promoting the learning and navigation of virtual mazes by 10 BVI users (Crossan and Brewster, 2006). In a study comparing learning of maritime environments between traditional tactile maps vs. virtual maps combining auditory sounds/labels and force-feedback using a Phantom device, six totally blind participants showed equivalent accuracy in triangulation of landmark configuration after exposure to both types of maps (Simonnet et al, 2011). Highly similar performance for describing topological relations by five BVI people was also demonstrated after learning an indoor multi-room environment with a traditional tactile map vs. a virtual simulation explored using a commercial Logitech force feedback joystick or mouse, with the most analogous results found with the haptic mouse (Nemec et al, 2004).…”
Section: Force Feedback Dimsmentioning
confidence: 99%